2022
DOI: 10.1088/1674-4527/ac3e5a
|View full text |Cite
|
Sign up to set email alerts
|

The Binarity of Early-type Stars from LAMOST medium-resolution Spectroscopic Survey

Abstract: Massive binaries play significant roles in many fields. Identification of massive stars, particularly massive binaries, is of great importance. In this paper, by adopting the technique of measuring the equivalent widths of several spectral lines, we identified 9,382 early-type stars from LAMOST medium-resolution survey and divided the sample into four groups, T1 ($\sim$O-B4), T2 ($\sim$B5), T3 ($\sim$B7), and T4 ($\sim$B8-A). The relative radial velocities $RV_{\rm rel}$ were calculated using the Maximum Likel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 84 publications
2
19
1
Order By: Relevance
“…Based on low-resolution observation from the LAM-OST DR5, Luo et al (2021) reported a binary fraction of 40% for O-and B-type stars in the sample using spectra with more than three observations. Later work by Guo et al (2022) utilizing the medium-resolution spectra with a cadence of more than two from the LAMOST DR7 suggests a binary fraction of 68% for the early-type OB stars.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on low-resolution observation from the LAM-OST DR5, Luo et al (2021) reported a binary fraction of 40% for O-and B-type stars in the sample using spectra with more than three observations. Later work by Guo et al (2022) utilizing the medium-resolution spectra with a cadence of more than two from the LAMOST DR7 suggests a binary fraction of 68% for the early-type OB stars.…”
Section: Introductionmentioning
confidence: 99%
“…In the work of Guo et al (2022) (Paper I hereinafter), the relative radial velocity is obtained by a Maximum Likelihood Estimation and a star is recognized as a binary according to the maximum variation of radial velocity. The intrinsic binary fraction can be obtained by correcting for any observational biases appearing in the sample using a series of Monte-Carlo simulations from Sana et al (2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major goal of this work is to identify CBe stars from the database. We selected the spectra of early-type stars from the archived sample following the procedures described in Guo et al (2022). We first adopted the estimated effective temperatures (T eff ) as given by the LAMOST stellar parameter pipeline (LASP; Wu et al 2014) to coarsely eliminate any late A-type to late F-type stars with 6500 K T eff 8000 K from the MRS sample.…”
Section: Selection Of Early-type Stars From the Mrs Databasementioning
confidence: 99%
“…This huge database brings the possibility to significantly expand the scale of the OB star sample. From the LAMOST Low Resolution Spectra (LRS), about 16,000 OB stars were identified by Liu et al (2019) and from the LAMOST Mid Resolution Spectra (MRS), other ∼9000 OB stars were then identified by Guo et al (2022). For these LAMOST-OB stars, the basic stellar parameters including the effective temperature (T eff ) and surface gravity ( g log ) were determined by Guo et al (2021) by the data-driven technique Stellar LAbel Machine (SLAM) with the non-LTE TLUSTY synthetic spectra as the training data set.…”
Section: Introductionmentioning
confidence: 99%